Hybrid Repair of a Common Carotid Pseudoaneurysm and Concomitant Internal Carotid Stenosis With Retrograde Stenting and Carotid Endarterectomy. (August 2021) - Zarmakoupis, Constantinos; Galyfos, George; Tsoukalos, Grigorios; Dalla, Panagiota; Triantafyllou, Alexandra; Zografos, Konstantinos; Sigala, Fragiska; Filis, Konstantinos
This report aims to present a rare case of a common carotid artery (CCA) pseudoaneurysm with a concomitant internal carotid artery (ICA) stenosis that were treated with a hybrid technique. This strategy included the retrograde placement of a CCA covered stent under ICA clamping followed by standardized carotid endarterectomy. The technique will be discussed and compared with other possible treatments.